Acetyl-CoA synthetase 2 promotes diabetic renal tubular injury in mice by rewiring fatty acid metabolism through SIRT1/ChREBP pathway - Lu Jian; Li Xue-qi; Chen Pei-pei; Zhang Jia-xiu; Li Liang; Wang Gui-hua; Liu Xiao-qi; Jiang Chun-ming; Ma Kun-ling (Acta Pharmacologica Sinica, 2024)
Diabetic nephropathy (DN) is characterized by chronic low-grade renal inflammatory responses, which greatly contribute to disease progression. Abnormal glucose metabolism disrupts renal lipid metabolism, leading to lipid accumulation, nephrotoxicity, and subsequent aseptic renal interstitial inflammation. In this study, we investigated the mechanisms underlying the renal inflammation in diabetes, driven by glucose-lipid metabolic rearrangement with a focus on the role of acetyl-CoA synthetase 2 (ACSS2) in lipid accumulation and renal tubular injury. Diabetic models were established in mice by the injection of streptozotocin and in human renal tubular epithelial HK-2 cells cultured under a high glucose (HG, 30 mmol/L) condition. We showed that the expression levels of ACSS2 were significantly increased in renal tubular epithelial cells (RTECs) from the diabetic mice and human diabetic kidney biopsy samples, and ACSS2 was co-localized with the pro-inflammatory cytokine IL-1β in RTECs. Diabetic ACSS2-deficient mice exhibited reduced renal tubular injury and inflammatory responses. Similarly, ACSS2 knockdown or inhibition of ACSS2 by ACSS2i (10 µmol/L) in HK-2 cells significantly ameliorated HG-induced inflammation, mitochondrial stress, and fatty acid synthesis. Molecular docking revealed that ACSS2 interacted with Sirtuin 1 (SIRT1). In HG-treated HK-2 cells, we demonstrated that ACSS2 suppressed SIRT1 expression and activated fatty acid synthesis by modulating SIRT1-carbohydrate responsive element binding protein (ChREBP) activity, leading to mitochondrial oxidative stress and inflammation. We conclude that ACSS2 promotes mitochondrial oxidative stress and renal tubular inflammation in DN by regulating the SIRT1-ChREBP pathway. This highlights the potential therapeutic value of pharmacological inhibition of ACSS2 for alleviating renal inflammation and dysregulation of fatty acid metabolic homeostasis in DN.